Challenging Global Development Towards Decoloniality and Justice - Melber, Henning; Kothari, Uma; Camfield, Laura; Biekart, Kees (EADI Global Development Series, 2024)
This open access book presents contributions to decolonize development studies. It seeks to promote and sustain new forms of solidarity and conviviality that work towards achieving social justice.Recognising global poverty and inequalities as historic injustices, the book addresses how these can be challenged through teaching, research, and engagement in policy and practice, and the sorts of political barriers these might encounter. From a variety of perspectives and contexts, these chapters examine how decoloniality and solidarity can be developed, offering in-depth historical, theoretical, epistemological, and empirical analyses.